Psychological Risk and Protective Factors among “Left-Behind” Children in The Context of Labor Migration in Uzbekistan: A Systematic Analysis - Shavkatovich, Shavkatov Shaxboz (American Journal of Biology and Natural Sciences, 2026)
Labor migration has become a structural socio-economic feature of modern Uzbekistan, resulting in millions of children being raised without the presence of one or both parents. This article provides a systematic analysis of the psychological risk and protective mechanisms for these "left-behind" children (LBC). By synthesizing global attachment theories with local socio-cultural dynamics and UNICEF statistics, the study identifies emotional deprivation as a primary risk factor, while the "extended family" is established as a critical buffer (protector). The findings emphasize the necessity of systemic psychological interventions to support the mental resilience of left-behind children in Central Asia.